Maternal Satisfaction with Intrapartum Nursing Care and Its Associated Factors among Mothers Who Gave Birth in Public Hospitals of North Wollo Zone, Northeast Ethiopia: Institution-Based Cross-Sectional Study - Asmamaw Demis; Ribka Nigatu; Derebe Assefa; Getnet Gedefaw (Hindawi Limited, 2020)
Background. Now a day, satisfaction had been identified as the major index to assess the quality of health-care provision in the world including Ethiopia. Mothers judge the quality of intrapartum care received based on their satisfaction with the services provided, thus influencing their utilization of the available health facilities. Therefore, this study aimed to assess maternal satisfaction with intrapartum care and associated factors among mothers who gave birth in public hospitals in North Wollo Zone, Northeastern Ethiopia, 2019. Methods. Institutional-based cross-sectional quantitative study was conducted in public hospitals of North Wollo Zone, and a total of 398 study participants were selected by using a systematic random sampling method. Data was collected using a standardized questionnaire by direct interviewing of study participants, and data was analyzed using SPSS 24 versions to determine the frequency of variables. Logistic regression was carried out to identify factors associated with maternal satisfaction. Results. From the total of 398 study participants, about 51% of women were satisfied with the hospital-based intrapartum nursing care. Being rural in residency (AOR: 2.03; 95% CI: 1.05-3.93), time to be seen by health-care providers (AOR: 2.82; 95% CI: 1.46-5.46), having history of ANC follow-up (AOR: 3.73; 95% CI: 1.12-12.57), and getting adequate meal (AOR: 3.96; 95% CI: 1.13-13.83) had showed statistical significant association with maternal satisfaction. Conclusion. In this study, the overall maternal satisfaction with intrapartum nursing care was low. Therefore, improving ANC follow-up, early examined by health-care providers, and getting adequate meal while in labour and delivery might enhance women satisfaction with intrapartum nursing care services.